AB1239 The detection of erosions in patients with rheumatoid arthritis by computer-aided joint space analysis. (23rd January 2014) - Pfeil, A.; Boettcher, J.; Lehmann, G.; Hansch, A.; Oelzner, P.; Wolf, G.
Abstract : Objectives: The aim of this study was to asses the Z-Score of computer-aided joint space analysis (CAJSA) as a novel approach for the quantification of finger joint space narrowing and its potential to quantify erosive disease in patients with rheumatoid arthritis (RA). Methods: 186 patients (133 female and 53 male) with a verified RAunderwent computerized semi-automated measurements of finger joint space width by the CAJSA-technique (Radiogrammetry Kit, Version 1.3.6) based radiographs. The Z-Score as an age and gender independent parameter of joint space narrowing was calculated and compared to the Sharp-van der Heijde (SHS) Score. Results: The Z-Scores of finger articulations in patients with RA were generally decreased. MCP-articulations showed a continuous significant decline of -1.65±0.30 SD dependent on SHS. The PIP-joints also revealed a significant reduction of the Z-Score (-0.96±0.31 SD). Additionally, the potential of the technique for detection of erosions was performed and presented a sensitivity and specificity of the Z-Score for JSD-MCP with 85.4% and 55.2%. Conclusions: The Z-Score shows the potential as a surrogate marker of RA progression which comprehends the early identification of patients with RA and inparticular those with erosive course of the disease, enabling a timely therapeutic strategy for cartilage protection. Disclosure of Interest: None Declared